Forest Restoration Potential in a Deforested Mountain Area: An Ecosociological Approach towards Sustainability - Stefan Zerbe; Lorenzo Pieretti; Susanne Elsen; Zezva Asanidze; Iveri Asanidze; Levan Mumladze (Forest Science, 2020)
Forest degradation worldwide stimulates efforts to restore forests. In particular, in mountain areas, where livestock agriculture and grazing have led to deforestation and a strong decrease in forest ecosystem services over centuries, it is necessary to develop sustainable strategies for the restoration of multifunctional forest ecosystems. We investigate the case study of the Javakheti Highland in the Southern Caucasus (Georgia), which is largely deforested because of long-lasting agricultural land use. We take into consideration the natural potential of forest development, the multifacetted potential of forest use, and those stakeholders directly and indirectly, respectively, involved in forest restoration. We show that neither the natural ecological site factors nor the potential of forest use, considering traditional and modern use, pose a limitation on forest restoration. Traditional ecological knowledge is still present, however hardly activated nowadays. However, social, cultural, and political obstacles have to be addressed for the development of a sustainable forest-management policy, which is rooted in the local communities. Environmental policy favoring forest development in Javakheti Highland should integrate national forest development policy with the perception, requirements, and traditions of local people.